Strategies for promoting Gender and Social Inclusion (GESI) in the agribusiness sector in Kenya: experiences from the field - Apondi, M.; Enokenwa Baa, Ojongetakah; Nortje, Karen (International Water Management Institute (IWMI), 2023)
This report aims to explore the intersection of gender and social inclusion, with a focus on the challenges and opportunities faced by women and youth in the agribusiness sector. It examines the ways in which gender norms and stereotypes shape social inclusion, and how exclusionary practices can perpetuate gender-based inequalities. The report draws on the gender analysis studies, baseline surveys and positive case study examples from diverse settings to highlight the key issues and strategies for promoting Gender and Social Inclusion (GESI) in the agribusiness sector. It also offers recommendations for policymakers, practitioners, and civil society actors to enhance gender-responsive approaches to social inclusion, and to ensure that marginalized groups are included in decision-making processes and benefit from development interventions and underscores the importance of addressing gender-based discrimination and promoting social inclusion as a means of advancing human rights and achieving sustainable development. These include measures such as inclusive disruptive innovation, equal involvement in policy making processes, inclusive market and production systems and representation in decision making. The report emphasizes that promoting GESI is not only a matter of social justice, but also essential for achieving sustainable development goals and building more resilient societies.